Prospects of Zinc Supplementation in Autism Spectrum Disorders and Shankopathies Such as Phelan McDermid Syndrome - Hagmeyer, Simone; Sauer, Ann Katrin; Grabrucker, Andreas M. (Frontiers in Synaptic Neuroscience, 2018)
The loss of one copy of SHANK3 (SH3 and multiple ankyrin repeat domains 3) in humans highly contributes to Phelan McDermid syndrome (PMDS). In addition, SHANK3 was identified as a major autism candidate gene. Interestingly, the protein encoded by the SHANK3 gene is regulated by zinc. While zinc deficiency depletes synaptic pools of Shank3, increased zinc levels were shown to promote synaptic scaffold formation. Therefore, the hypothesis arises that patients with PMDS and Autism caused by Shankopathies, having one intact copy of SHANK3 left, may benefit from zinc supplementation, as elevated zinc may drive remaining Shank3 into the post-synaptic density and may additional recruit Shank2, a second zinc-dependent member of the SHANK gene family. Further, elevated synaptic zinc levels may modulate E/I ratios affecting other synaptic components such as NMDARs. However, several factors need to be considered in relation to zinc supplementation such as the role of Shank3 in the gastrointestinal system - the location of zinc absorption in humans. Therefore, here, we briefly discuss the prospect and impediments of zinc supplementation in disorders affecting Shank3 such as PMDS, and propose a model for most efficacious supplementation.